Penguatan Minat Belajar Siswa dalam Konteks Emosional Spiritual Quotient pada Pembelajaran Pendidikan Agama Islam - Jannah, Eni Mifta; Zailani, Zailani; Ruslan, Muhammad (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
Islamic Religious Education learning is still focused on memorization aspects without providing sufficient space for thinking, this makes students' interest in exploring, questioning and discussing PAI materials actively still low, which ultimately many students take PAI lessons merely to fulfill academic obligations, and PAI learning has not consistently touched the emotional and spiritual aspects of students, resulting in many students not understanding Islamic values ​​​​completely both logically and emotionally. The purpose of this study is to analyze the condition of students'interest in learning PAI, analyze the application of ESQ in PAI learning, and identify factors that inhibit the strengthening of students' interest in learning in the context of ESQ in PAI learning. This research uses a qualitative approach with a descriptive study type. The results of this study indicate that strengthening learning interest in the context of ESQ in Islamic Religious Education learning has been implemented, as evidenced by their increasing enthusiasm, confidence, and deeper understanding of religious values ​​when learning is implemented with a variety.